Cognitive load and autonomic response patterns under negative priming demand in depersonalization‐derealization disorder. (15th February 2016) - Lemche, Erwin; Sierra‐Siegert, Mauricio; David, Anthony S.; Phillips, Mary L.; Gasston, David; Williams, Steven C.R.; Giampietro, Vincent P.
Abstract: Previous studies have yielded evidence for cognitive processing abnormalities and alterations of autonomic functioning in depersonalization‐derealization disorder (DPRD). However, multimodal neuroimaging and psychophysiology studies have not yet been conducted to test for functional and effective connectivity under cognitive stress in patients with DPRD. DPRD and non‐referred control subjects underwent a combined Stroop/negative priming task, and the neural correlates of Stroop interference effect, negative priming effect, error rates, cognitive load span and average amplitude of skin conductance responses were ascertained for both groups. Evoked haemodynamic responses for basic Stroop/negative priming activations were compared. For basic Stroop to neutral contrast, patients with DPRD differed in the location (inferior vs. superior lobule) of the parietal region involved, but showed similar activations in the left frontal region. In addition, patients with DPRD also co‐activated the dorsomedial prefrontal cortex ( BA 9) and posterior cingulate cortex ( BA 31), which were also found to be the main between‐group difference regions. These regions furthermore showed connectivity with frequency of depersonalization states. Evoked haemodynamic responses drawn from regions of interest indicated significant between‐group differences in 30–40% of time points. Brain‐behaviour correlations differed mainly in laterality, yet only slightly in regions. A reversal of autonomic patterning became evident in patients with DPRD for cognitive load spans, indicating less effective arousal suppression under cognitive stress – patients with DPRD showed positive associations of cognitive load with autonomic responses, whereas controls exhibit respective inverse association. Overall, the results of the present study show only minor executive cognitive peculiarities, but further support the notion of abnormalities in autonomic functioning in patients with DPRD. Abstract : The neural bases and autonomic response patterns of cognitive load occupying working memory have different functional activation locations in the prefrontal cortex and different sympathetic arousal suppression intensities in Depersonalisation‐Derealisation patients as compared to healthy controls. Cognitive load spans of working memory, which have not been neuroimaged previously, were derived from a combined Negative Priming/Stroop paradigm, combined with concurrent derivation of skin conductance responses indicative of sympathetic arousal.